Mathematical drying kinetics modeling of jackfruit seeds (Artocarpus heterophyllus Lam.) - Leite, Daniela; Queiroz, Alexandre José; Figueirêdo, Rossana Maria; Lima, Leiliane (Revista Ciência Agronômica, 2019)
Jackfruit (Artocarpus heterophyllus Lam.) is a fruit with pulp rich in carbohydrates, calcium, phosphorus, iron and B-complex vitamins. A large amount of waste is generated in the pulp processing, in which the seeds are included. Jackfruit seeds are often consumed after cooking, and may also undergo roasting, milling and incorporation into bakery products. The remaining jackfruit seeds can be germinated as a means to increase its utilization, constituting a process that confers positive biochemical modifications to the nutritional quality. Thus, the objective of this work was to dry the germinated seeds of the jackfruit tree in a convective drier at 55, 65 and 75 °C with drying air velocities of 1.0 and 1.3 m s-1, and adjusting different mathematical models to the experimental data. The Two-Terms model presented the best adjustment parameters among the ten mathematical models tested, resulting in the most adequate model to represent the drying behavior. The effective diffusivity increased with the increase in temperature, being in the order of 10-7 m2 s-1.